Evaluating the impact of leaf trichome on whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) dynamics in cassava - Prombut, Supawadee; Wangkeeree, Jureemart; Roddee, Jariya (Food Agricultural Sciences and Technology, 2026)
Cassava (Manihot esculenta) is a vital crop in Thailand. However, its yield is significantly impacted by Cassava Mosaic Disease (CMD), caused by the Sri Lankan Cassava Mosaic Virus (SLCMV). CMD is primarily spread by whiteflies (Bemisia tabaci), as whitefly infestations facilitate disease transmission; therefore, understanding pest resistance in cassava is crucial. Antixenosis, a form of resistance, involves plant traits such as trichome density that deter pest colonization. This study evaluated trichome density and size across six cassava cultivars—Huaybong 60, CMR 89, Kasetsart 50, Rayong 72, Rayong 4, and Pirun 2—and assessed their influence on whitefly settling preferences. Whitefly populations were monitored for four months, while trichome density and size were analyzed using scanning electron microscopy (SEM). The results indicated significant variation in whitefly infestation among the cassava cultivars. The CMR 89, Pirun 2, Rayong 4, and Kasetsart 50 cultivars experienced the highest infestation, whereas Huaybong 60 and Rayong 72 had lower infestations. Notably, the Huaybong 60 displayed the highest trichome density, followed by Rayong 72, Pirun 2, and CMR 89, while Rayong 4 and Kasetsart 50 had lower densities. A strong negative correlation was observed between trichome density and whitefly infestation, suggesting that higher trichome density effectively reduces whitefly colonization. These findings indicate that Huaybong 60 and Rayong 72 could serve as promising genetic resources for breeding cassava cultivars with enhanced non-preference resistance (antixenosis) to whiteflies. This research highlights the importance of selecting resistant cultivars to strengthen cassava production while minimizing the impact of whitefly-transmitted diseases.